A Comprehensive Analysis of Multilingualism, Typology, and Language Dynamics in Contemporary Indonesia - Nurasia Natsir; Kamsinah Kamsinah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Indonesia represents one of the world's most complex and dynamic linguistic ecosystems, harboring over 700 regional languages alongside the national language (Bahasa Indonesia) and Indonesian Sign Language (BISINDO). This synthesis study provides comprehensive analysis of the Indonesian linguistic landscape, integrating findings from five complementary large-scale investigations conducted 2020–2024: code-switching patterns in digital communication; typological uniqueness of Indonesia's tenseless temporal system; linguistic complexity of BISINDO and barriers to deaf inclusion; sociolinguistic stratification through first-person pronoun variation; and critical endangerment of regional languages. The synthesis employed integrative methodology encompassing 3,550 total participants, 20,000+ linguistic tokens, 18 months of ethnographic fieldwork, and analysis of 150 languages and 25 revitalization programs. Synthesis reveals five interconnected dynamics: (1) centripetal standardization through education, urbanization, and media; (2) centrifugal diversification through identity construction and social stratification; (3) typological persistence maintaining Indonesian distinctiveness despite contact; (4) parallel endangerment affecting regional languages and BISINDO; and (5) ideology-driven change linking language choice to modernity and prestige. These dynamics produce dynamic tension between homogenization and diversification. Indonesia's linguistic future depends on whether policies can balance national unity through Indonesian and linguistic diversity through regional language and BISINDO protection.